2018
DOI: 10.1016/j.gaitpost.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Gait kinetics in children with clubfeet treated surgically or with the Ponseti method: A meta-analysis

Abstract: Differences in gait kinetics are present when comparing Ponseti treated clubfeet with healthy controls. However, there is no significant difference between surgically and Ponseti treated clubfeet. These results give more insight in the possibilities of improving the gait pattern of patients treated for clubfeet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
(76 reference statements)
0
9
0
Order By: Relevance
“…The general treatment of talipes equinus is correction, performed more than once, with a cast and mold support [18]. The Ponseti method is the gold standard for the treatment of talipes equinus [19][20][21]. The Ponseti method has a more pronounced correction rate in the treatment of talipes equinovarus than the Kite method [22].…”
Section: Introductionmentioning
confidence: 99%
“…The general treatment of talipes equinus is correction, performed more than once, with a cast and mold support [18]. The Ponseti method is the gold standard for the treatment of talipes equinus [19][20][21]. The Ponseti method has a more pronounced correction rate in the treatment of talipes equinovarus than the Kite method [22].…”
Section: Introductionmentioning
confidence: 99%
“…A statistically significant difference in mean of inversioneversion and dorsi-plantar flexion after surgery when compared with controls was shown. In a recent meta-analysis, Tuinsma et al found that kinematics of gait was comparable between clubfeet treated by surgery or the Ponseti method [23]. However, the higher range of ankle dorsiflexion found in our clubfoot patients could be due to the technique of z-lengthening of tendoachilles.…”
Section: Discussionmentioning
confidence: 55%
“…The soft tissue release procedure remains a feasible option for idiopathic clubfoot, although its indication is currently limited [2,3,23]. In this report, we evaluated the surgical results of idiopathic clubfoot patients aged older than five years, the age when a child achieved a fully mature gait [11,20].…”
Section: Discussionmentioning
confidence: 99%
“…The Ponseti method is considered to be the gold standard for clubfoot treatment [1][2][3]. However, relapse and residual gait deviations are common, even after successful initial treatment [3][4][5], and children with clubfoot are recommended to undergo clinical follow-up at least until the age of 7 years [6]. Different measures are used to evaluate clubfoot status [7][8][9][10][11][12][13], but there is a lack of agreement about which measurements are the most appropriate [14].…”
Section: Introductionmentioning
confidence: 99%